2019
DOI: 10.1002/adma.201807313
|View full text |Cite
|
Sign up to set email alerts
|

3D Printed High‐Performance Lithium Metal Microbatteries Enabled by Nanocellulose

Abstract: Batteries constructed via 3D printing technique have inherent advantages including the opportunities for miniaturization, autonomous shaping, and controllable structural prototyping. However, 3D printed lithium metal batteries (LMBs) have not yet been reported due to the difficulties of printing lithium (Li) metal. Here, for the first time, we fabricated high-performance LMBs by a 3D printing technique using cellulose nanofiber (CNF), which is one of the most earth abundant biopolymers. The unique shear thinn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
208
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 263 publications
(211 citation statements)
references
References 43 publications
2
208
0
1
Order By: Relevance
“…3D‐printing technologies have been extensively used in different research fields such as energy storage devices, catalysis, electronics, microfluidics, and biotechnology . These printing technologies have enabled the creation of unique material and device structures that cannot be achieved by conventional methods . Moreover, by exploring new complex architectures, these 3D‐printed materials can achieve novel and/or improved functionality.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…3D‐printing technologies have been extensively used in different research fields such as energy storage devices, catalysis, electronics, microfluidics, and biotechnology . These printing technologies have enabled the creation of unique material and device structures that cannot be achieved by conventional methods . Moreover, by exploring new complex architectures, these 3D‐printed materials can achieve novel and/or improved functionality.…”
Section: Methodsmentioning
confidence: 99%
“…Direct ink writing (DIW) is one of the most commonly used 3D‐printing techniques. It offers great flexibility in the material (ink) selection and has been recently applied to prepare electrodes for electrochemical energy storage devices, including lithium‐ion batteries, sodium‐ion batteries, lithium–sulfur batteries, lithium metal batteries, and supercapacitors . In comparison to bulk electrodes, these 3D‐printed electrodes have shown improved electrolyte infiltration and ion diffusion …”
Section: Methodsmentioning
confidence: 99%
“…An additive design approach can be defined as an electrode that is built by adding the electrode slurry via a layer by layer process, which is a technique commonly referred to as extrusion‐type 3D printing or direct ink writing . This endows researchers a fast and cost‐effective method for the fabrication of 3D electrodes with precise construction and tunable architecture.…”
Section: Electrode Design and Processing: Tortuositymentioning
confidence: 99%
“…Additionally, these materials possess a relatively high molten state temperature, increasing the complexity of the manufacturing process and energy consumption. In a recent study, Cao et al reported lithium‐metal microbatteries based on cellulose nanofibers (CNFs) . CNF possesses high solubility in water owing to the rich presence of hydroxyl groups on the cellulose molecules .…”
Section: Electrode Materials For 3d‐printed Batteriesmentioning
confidence: 99%
“…f) Optical image of a packaged battery to power an LED. Reproduced with permission . Copyright 2019, Wiley‐VCH.…”
Section: Electrode Materials For 3d‐printed Batteriesmentioning
confidence: 99%